Novel Hydrogen Sulfide Hybrid Derivatives of Keap1-Nrf2 Protein-Protein Interaction Inhibitor Alleviate Inflammation and Oxidative Stress in Acute Experimental Colitis - Xian Zhang; Keni Cui; Xiaolu Wang; Yuanyuan Tong; Chihong Liu; Yuechao Zhu; Qidong You; Zhengyu Jiang; Xiaoke Guo (MDPI AG, 2023)
Ulcerative colitis (UC) is an idiopathic inflammatory disease of unknown etiology possibly associated with intestinal inflammation and oxidative stress. Molecular hybridization by combining two drug fragments to achieve a common pharmacological goal represents a novel strategy. The Kelch-like ECH-associated protein 1 (Keap1)-nuclear factor erythroid 2-related factor 2 (Nrf2) pathway provides an effective defense mechanism for UC therapy, and hydrogen sulfide (H2S) shows similar and relevant biological functions as well. In this work, a series of hybrid derivatives were synthesized by connecting an inhibitor of Keap1-Nrf2 protein-protein interaction with two well-established H2S-donor moieties, respectively, via an ester linker, to find a drug candidate more effective for the UC treatment. Subsequently, the cytoprotective effects of hybrids derivatives were investigated, and DDO-1901 was identified as a candidate showing the best efficacy and used for further investigation on therapeutic effect on dextran sulfate sodium (DSS)-induced colitis in vitro and in vivo. Experimental results indicated that DDO-1901 could effectively alleviate DSS-induced colitis by improving the defense against oxidative stress and reducing inflammation, more potent than parent drugs. Compared with either drug alone, such molecular hybridization may offer an attractive strategy for the treatment of multifactorial inflammatory disease.